Suitability of preparation exercises for training of Tkachev on high bar - Kalichova, M. (International Scientific Congress Slovenian Gymnastics Federation, 2019)
Preparation exercises are used when learning gymnastic elements. The aim of the study was to compare similarity of preparation exercises with the final form of the selected element Tkachev in gymnasts at different levels of mastering of the movement structure. 3 male artistic gymnasts of junior category were included in the study. 3-Axis accelerometers attached to the bar was used to record the movement. A program Signalplant with cross correlation coefficient was used to evaluate the data. The results showed statistically significant similarity between the preparatory giant circles and the final element Tkachev. In gymnast 1 with the lowest performance level higher similarity of preparation exercises with unsuccessful attempts of Tkachev was found. In gymnast 2 and 3 the similarity of preparation exercise with successful attempts on Tkachev increased with their performance level. Based on the results we recommend including preparation exercises when learning this complex movement structure.